Structural and phase composition modification of nanocrystalline Nd14Fe79B7 alloy during thermomagnetic measurements - Talijan N.; Ćosović V.; Žák T.; Grujić A.; Stajić-Trošić J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Changes in the microstructure parameters, phase composition and magnetic properties of rapid quenched Nd-rich Nd14Fe79B7 alloy caused by thermomagnetic measurement (TM) were studied using XRD methods of phase analysis, crystallite size and lattice microstrain determination. The observed changes were analyzed between the optimized magnetic state of this alloy and state after TM up to 800oC. Measurement of magnetic properties was carried out on the SQUID magnetometer at ambient temperature. The obtained experimental results show that the investigated alloy in the optimized magnetic state has nearly monophase composition with predominant content of hard magnetic Nd2Fe14B phase (up to 95 mass %) with mean crystallite size below 60 nm. In the state after TM, it was found that the decreased amount of Nd2Fe14B phase (75 mass%), increased amount of soft magnetic phases, predominantly of Fe7Nd5, formation of Nd-rich oxide Nd2O3 phase, as well as grain growth have caused the observed quality loss of hard magnetic properties.